STUNTING PREVENTION THROUGH EMPOWERING PREGNANT WOMEN AND MOTHERS OF TODDLERS - Dewi, Ratna Sari; Wardani, Emi Kusuma (Library Unit collaborates with the Institute for Research and Community Service, College of Health Sciences Husada Jombang, 2024)
Background: Stunting is a global issue, affecting 178 million children under five years old. In Indonesia, the prevalence of stunting remains high, with 30.8% of toddlers affected. Objective: This community service aimed to increase knowledge about stunting prevention among pregnant women and mothers of toddlers. Method: The educational activities, including lectures, discussions, and demonstrations, were conducted with 20 participants in the Dukunyar Village, Dukun District, Gresik Regency. Results: The results significantly improved participants' knowledge about stunting prevention. Conclusion: This suggests that educational interventions are effective in raising awareness about stunting prevention among vulnerable groups.